2007
DOI: 10.1097/acm.0b013e3180674af2
|View full text |Cite
|
Sign up to set email alerts
|

The Advisory Dean Program: A Personalized Approach to Academic and Career Advising for Medical Students

Abstract: Advising and mentoring programs for medical students vary in their official names, scope, and structures. Catalyzed by negative student feedback regarding career advising and a perceived disconnection between faculty and students, in academic year 2003-2004, Columbia University College of Physicians and Surgeons implemented its formal Advisory Dean (AD) Program and disbanded its former advising system that used faculty volunteers. The AD Program has become a key element for enhancing the students' professional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 10 publications
0
65
0
3
Order By: Relevance
“…However, their system focused primarily on career advising and planning, while our study also demonstrated a significant impact on student wellness. Many of the other innovative college advising systems above report that formative surveys and focus groups have shown that students value these interventions (Puckett et al 1989;Kalet et al 2002;Scheckler et al 2004;Goldstein et al 2005;Macaulay et al 2007). However, these institutions have not published data regarding overall effectiveness in reaching their goals or compared the results to more traditional advising systems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, their system focused primarily on career advising and planning, while our study also demonstrated a significant impact on student wellness. Many of the other innovative college advising systems above report that formative surveys and focus groups have shown that students value these interventions (Puckett et al 1989;Kalet et al 2002;Scheckler et al 2004;Goldstein et al 2005;Macaulay et al 2007). However, these institutions have not published data regarding overall effectiveness in reaching their goals or compared the results to more traditional advising systems.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, oneon-one mentoring is encouraged between advisory directors and their students. Columbia University College of Physicians and Surgeons has created a similar Advisory College System that engages students in bi-monthly meetings and provides additional mentoring as needed (Macaulay et al 2007). Kalet et al (2002) describe the implementation of an advisory program at NYU (New York University) School of Medicine whose colleges are theme based and therefore attract faculty members and students with similar interests and goals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mentors are able to encourage career aspirations, create networking opportunities, increase self-confidence, and socialize mentees into the profession. 1,2 Mentoring is also a vital component in the development of professionalism, [2][3][4] and professional students reported that mentoring was important to them. In developing these relationships, faculty members can participate in formal programs that involve students and residents as well as interact informally with them outside the academic setting.…”
Section: Introductionmentioning
confidence: 99%
“…In general, however, the primary goal of these programs is to enhance the overall medical school experience for students. [1][2][3][4][5][6] The traditional medical training environment is characterized by an intense workload, a competitive and individualisCorrespondence: Rachel B. Levine, Division of General Internal Medicine, Johns Hopkins Bayview Medical Center 5200 Eastern Ave. /Mason F. Lord Bldg, Center Tower, Suite 2300, Baltimore, MD 2122. Email: rlevine@jhmi.edu tic culture, and high learner stress.…”
Section: Introductionmentioning
confidence: 99%